Quasi-partnership forms of state-business interaction in innovative development - M. A. Valishvili (Вестник университета, 2022)
Implementation of the significant social and economic projects in Russia in the context of economic downturn caused by the COVID-19 pandemic rises a search of new mutually beneficial forms of state-business cooperation. Traditional forms of this such as concession agreements and public-private partnerships agreements have shown high sensitivity to the crisis phenomena in the Russian economy, when a number of projects has been suspended due to a significant reduction in consumer demand and rising costs, which has created a high-level risk that projects will not achieve their final goals. The purpose of the research is to study institutional framework of state-business interaction in the implementation of economic development projects, including based on quasi-partnership forms. To quantitatively characterise this process development in the Russian economy, author uses an assessment of the statistical performance indicators dynamics for the technology-innovative type special economic zones, which are a quasi-partnership state-business interaction form. The necessity and efficiency of the quasi-partnership state-business interaction practice in such zones have been proved. The research results demonstrate a new potential of the public-private partnerships in innovation projects.